Inter-Gender Pelvic Shape Variations as a Cause of DDH Overdiagnosis - Abdalla KM (Dove Medical Press, 2020)
Khalid M Abdalla,1 Mostafa A Abdelrahman,2 Abdelwahab J Aleshawi,3 Alaha S Al Taweel,1 Majid Bani-Ata,4 Khaled Obeidat5 1Department of Diagnostic Radiology and Nuclear Medicine, Faculty of Medicine, Jordan University of Science and Technology, Irbid 22110, Jordan; 2Department of Allied Medical Sciences, Faculty of Applied Medical Sciences, Jordan University of Science and Technology, Irbid 22110, Jordan; 3Department of Special Surgery, Ophthalmology Division, Jordan University of Science and Technology, Irbid 22110, Jordan; 4Department of Special Surgery, Otolaryngology Division, Faculty of Medicine, Jordan University of Science and Technology, Irbid 22110, Jordan; 5Department of General Surgery, Faculty of Medicine, Jordan University of Science and Technology, Irbid 22110, JordanCorrespondence: Khalid M AbdallaDepartment of Diagnostic Radiology and Nuclear Medicine, Faculty of Medicine, Jordan University of Science and Technology, P. O. Box: 3030, Irbid 22110, JordanTel +962 799273019Fax +962 2 7201064Email khalidmohabdalla@yahoo.comObjective: Developmental dysplasia of the hip (DDH) is an abnormal relationship between the acetabulum and the head of the femur. Plain x-ray of both hips at the age of 3 months is still in use in some countries. On plain films, classic lines and angles are evaluated to meet current guidelines for positive DDH. Among these is the acetabular angle (AA), which most did not exceed 30° in normal pelvis regardless of gender. A flat promontory gives the impression of a high AA angle, whereas a sharp promontory gives the impression of a low AA angle.Materials and Methods: All anteroposterior (AP) pelvic digital x-ray studies performed to rule out DDH were collected from the PACS systems. A novel angle was measured between a line parallel to the lateral aspect of the region of the inferior iliac spines and a line that extends along the acetabular roof to quantify the roundness of the iliac promontory. We called the former line the Miral line and the formed angle the iliac promontory angle.Results: We show that the promontory shape is significantly different between genders, and therefore it is mistaken to generalize an upper AA limit for males and females. In addition, we show that the current guideline of the upper limit of AA did not predict the incidence of DDH.Conclusion: We suggest that the current practice is introducing a high rate of false positive, especially among females, and the current guidelines on AA should be reviewed and assigned separately for males and females. This is more important for countries that did not utilize the ultrasonographic assessment for DDH.Keywords: acetabular angle, DDH, plain x-ray, head of the femur